Evaluation Of Pedigree Goats In Wooly Goat Farming (Eurasian Research Bulletin, 2022)
The article provides information and feedback on the establishment of lines from the gene pool of Angor breed goats, the use of selection methods in selection activities, and goat breeding evaluation.